Emission of Highly Activated Soot Particulate—The Other Side of the Coin with Modern Diesel Engines1. Issue 10 (10th January 2013) - Frank, Benjamin; Schuster, Manfred E.; Schlögl, Robert; Su, Dang Sheng
<x xml:space="preserve">Abstract</x> Soot toxification: The increasing chemical activity of the emitted soot particulate produced by modern diesel engines is an unwanted side effect of modification of the motors. This makes Euro IV and VI soots chemically and biologically highly active and hazardous. Taking these factors into consideration, the question arises whether the reduced net mass of diesel soot particulate emitted overcompensates for the induced micro‐ and nanostructure.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>